Studies on the use ofEchinostoma revolutum larvae as an agent for biological control of Fasciola gigantica - Estuningsih, Sarwitri Endah (Indonesian Journal of Animal and Veterinary Sciences, 1998)
The use of Echinostoma revolutum larvae as an agent for biological control of Fasciola gigantica has been studied in the laboratory of Parasitology, Balitvet. Infection of Lymnaea rubiginosa with Echinostoma revolutum increased the growth and mortality rates of the snails and completely suppressed their egg production . These effects were attributed to a destruction of gonads and other organs of the snails by echinostome rediae, production of which commenced during the second week after the infection. From laboratory studies with L. rubiginosa, there was an evidence of strong antagonism between larvae of E. revolutum and larvae of F. gigantica. Concurrent infection of L. rubiginosa with miracidia of F. gigantica and E. Revolutum resulted in that all snails were infected with E. revolutum only, when they were dissected 30 days later. In contrast, 94% of the snails which were exposed to miracidia of F. gigantica only, were infected with larvae of this species after 30 days . When L. rubiginosa were infected with F. gigantica 20 days previously were exposed to infection with E. revolutum and examined 30 days later, it was found that 77% of the snails had a single infection with E. revolutum, 16 % were infected with F. Gigantica only, and the remaining 7% had common infection. It was concluded that the dominant antagonism of E. revolutum over F. gigantica in L. rubiginosa and the reduction of fecundity and longevity ofsnails infected with E. revolutum could be useful for biological control of F. gigantica. Â  Key. words: Echinostoma revolutum, Fasciola gigantica, biological control, ducks, chickens